Effect of Cyclosporine on the Relevant Biochemical Parameters in Renal Transplantation Patients in Mosul/Iraq - Suad Alkass; Shehab Yousif; Mohammed Hamid; Alaa Alhamadany (College of Education for Pure Sciences, 2013)
ABSTRACT Cyclosporine (sandimmune) is the backbone of immunosuppression in renal transplantation. However, it leads to multiple side effects, most of which are dose-dependent. In this respect, the quality of renal functions is undoubtedly linked to cyclosporine drug levels.  Blood sample from 44 kidney-transplant recipients and 28 healthy control were collected, then serum Urea, Creatinine, Sodium (Na+), Potassium(K+), Cholesterol, Triglyceride, HDL-c, LDL-c, VLDL-c, Glutathione GSH and Malondialdehyde MDA were estimated. The current study showed that serum Cholesterol, TG, HDL-c, LDL-c and VLDL-c were significantly increased in renal transplantation patients comparing with the control group, The result also has been revealed that GSH concentration was decreased in renal recipient patients while MDA was increased renal recipient patients as comparing with the control group. On other hand Cholesterol, Triglyceride, HDL-c, LDL-c, VLDL-c, and MDA exhibited a weak correlation with dose of cyclosporine while GSH exhibibted reciprocal correlation with CsA dose.